ZIF-4 - Ryder, M. (My University, 2014)
Inelastic Neutron Scattering spectrum of ZIF-4, [Zn(C3H3N2)2]2, measured on the TOSCA instrument. Zinc imidazolate framework (ZIF). Imidazolate linker.
Keywords: TOSCA